Nivolumab-induced hypophysitis leading to hypopituitarism and secondary empty sella syndrome in a patient with non-small cell lung cancer. Issue 3 (7th March 2019) - Chang, Jeremy; Tran, Jeffrey; Kamel, Dina; Basu, Arnab
Abstract : We describe the clinical course of a 64-year-old woman with stage IVa lung adenocarcinoma who presented with over 1 month of fatigue, unintentional weight loss and emesis. She initiated treatment with nivolumab immunotherapy 1 year prior and had been tolerating the treatment well. A comprehensive workup revealed multiple endocrinological abnormalities consistent with hypophysitis leading to hypopituitarism in the form of central adrenal insufficiency and hypogonadism as well as a partially empty sella on imaging. This case demonstrates that while receiving novel forms of treatment such as immunotherapy, patients should be monitored closely for a wide range of adverse effects.